Soil Water Surplus in Salado River Basin and Its Variability during the Last Forty Years (Buenos Aires Province, Argentina) - Scarpati, Olga Eugenia (2011)
Soil water surplus and deficit occur frequently in Buenos Aires province in Argentina. This paper analyses the soil water surplus in a sub-area, the Salado River basin, in the period 1968-2008. This basin is divided in seven drainage areas, delimitated according to the National Water Resources. The series of soil water surplus data were adjusted by means of the theoretical normal cubic-root probability distribution, and the mean areal soil water surplus value of 300 mm was considered as a threshold above which floods can cause severe damage. An increase in the frequency of extreme events and in their tendency exists during the recent years, coherent with the increase of precipitation recorded in the region. The statistical significance of the results was assessed using the Mann Kendall and MAKESENS tests. The results showed a relevant temporal variability, but did not show significant tendencies.